Analysis of Students’ Difficulties in Developing Argumentative Essay - Bambela, Musdhalifa Muslima; Basalama, Nonny; Bantulu, Yusna (Research Review: Jurnal Ilmiah Multidisiplin, 2022)
This study is aimed to explore the students' difficulties in developing an argumentative essay in Writing for Academic Purposes Subject in of English Department, Universitas Negeri Gorontalo. The participants of this research are the students of class C, which consists of 8 students in the 5th semester of the academic year 2019/2020. Using a qualitative method that data were obtained from the semi-structured interview. This study also used Braun and Clarke's (2006) theory as the technique for analyzing the data. Therefore, the interview questions were adapted and developed from Creswell (2002). As a result of this research, the students, when they are writing an argumentative essay, still face difficulties although they have already passed the material. Besides, the students have various difficulties such as difficulty determining the topic, difficulty using the academic word, difficulty collecting data and information, and some students lack understanding of how to write an essay.